Universal conservation law governing the wave–particle duality and quantum entanglement - Kai Sun; Jin-Shi Xu; Chuan-Feng Li (Light: Science & Applications)
Abstract Universal conservation laws of wave–particle–entanglement triad, which describe relations between the wave–particle duality of a quantum system and its entanglement with an ancilla quantum memory, are proposed and further demonstrated with silicon-integrated nanophotonic chips.